Emerging technologies and materials in female hormone monitoring - Ylinen, Jerry (My University, 2024)
In health research and technology, understanding female physiology and hormones is important. Importance is underlined with the underrepresentation of women and the increasing need for rapid development in the field. This thesis introduces the crucial role of the four main hormones: luteinizing hormone (LH), follicle stimulating hormone (FSH), estrogens and progesterone, with a focus on estradiol as primary estrogen. Female hormone monitoring extends to fertility, hormonal assessment, drug dosing, and overall health and wellbeing monitoring. However, traditional science is often male dominated. This has led to an imbalance in health research. Female physiology and hormones have not been considered enough, resulting in challenges particularly in medication development. Here, male-centric data is typically extrapolated for all patients, and this has led to side effects on female patients. Technical challenges and the lack of at-home female hormone monitoring are conceded mainly due to the lack of accurate and non-invasive methods in the market. To address these issues, the thesis goes into the emerging technologies and materials to further advance the field. Wearable sensors are promising technological devices for continuous monitoring, while material development offers enhanced sensor sensitivity and selectivity. Materials combined with nanoparticles or biological elements offer potential for developing highly sensitive hormone sensors. The objective of this document is to highlight the need for advancements in female hormone monitoring, present new methods and technologies, and explore new materials in the field. By comprehensively going through the current state of the female hormone monitoring field and technologies, this study aims to give information about the challenges and opportunities for future directions.

Terveystutkimuksessa ja -teknologiassa naisten fysiologian ja hormonien ymmärtäminen on tärkeää. Tämä on tärkeää, koska naiset ovat aliedustettuina ja alalla on tarve nopealle kehitykselle. Tässä kandidaattityössä käsitellään neljää tärkeintä naisten hormonia: luteinisoivaa hormonia (LH), follikkelia stimuloivaa hormonia (FSH), estrogeenia ja progesteronia., keskittyen ensisijaisesti estradioliin pää estrogeenina. Naishormonien seuranta ulottuu hedelmällisyyteen, hormonaaliseen monitorointiin, lääkkeiden annosteluun sekä yleisen terveyden ja hyvinvoinnin seurantaan. Perinteinen tiede on kuitenkin usein miesvaltaista. Tämä on johtanut epätasapainoon terveystutkimuksessa. Naisten fysiologiaa ja hormoneja ei ole otettu riittävästi huomioon, mikä on johtanut haasteisiin erityisesti lääkekehityksessä. Lääkekehityksessä on ekstrapoloitu mieskeskeistä dataa, mikä on johtanut sivuvaikutuksiin naispotilailla. Tekniset haasteet ja naishormonien kotiseurannan puute johtuvat pääasiassa siitä, että markkinoilla ei ole tarkkoja ja ei-invasiivisia menetelmiä. Näiden ongelmien ratkaisemiseksi tutkielmassa tarkastellaan uusia tekniikoita ja materiaaleja, joiden avulla alaa voidaan kehittää edelleen. Puettavat sensorit tarjoavat lupaavia tekniikoita jatkuvaan seurantaan, kun taas materiaalien kehittäminen parantaa sensoreiden herkkyyttä ja selektiivisyyttä. Nämä materiaalit yhdistettynä nanohiukkasiin tai biologisiin elementteihin tarjoavat mahdollisuuksia kehittää erittäin herkkiä hormoniantureita. Tämän työn tavoitteena on korostaa naisten hormoniseurannan kehittämistarvetta, esitellä uusia menetelmiä ja teknologioita, sekä tutkia uusia materiaaleja. Naishormoni seurannan ja tekniikoiden nykytilaa käydään läpi. Työssä pyritään myös antamaan tietoa tulevaisuuden haasteista ja mahdollisuuksista.
Keywords: luteinizing hormone, follicle stimulating hormone, progesterone, estrogen, estradiol immunoassay, chromatography, wearable sensors, sampling, invasive, non-invasive, graphene, carbon nanotube, aptamer, luteinisoiva hormoni, follikkelia stimuloiva hormoni, progesteroni, estrogeeni, estradioli, immunomääritys, kromatografia, puettavat sensorit, näytteenotto, invasiivinen, ei-invasiivinen, grafeeni, hiilinanoputki, aptameeri